Risk Regulation and Deliberation in EU Administrative Governance—GMO Regulation and Its Reform. Issue 5 (24th May 2015) - Weimer, Maria
Abstract The article analyses the problems of EU risk regulation of genetically modified organisms (GMOs) through the lens of deliberative theories of EU law and governance, such as deliberative supranationalism and experimentalist governance. Previous research had suggested that the GMO issue is not conductive to deliberation within EU institutions because of its high politicisation. This article argues that another equally salient factor is the scientification of the GMO authorisation process. Scientification stands for the Commission's overreliance on epistemic legitimacy as the basis for risk management. Given the deadlock of comitology in this field, scientification is exacerbated by a reversion to top‐down regulation by the Commission. As a result, political responsibility for GMO authorisations gets lost. This article argues that both scientification and politicisation are mutually accelerative processes ultimately leading to a break down of dialogue at the EU level. This contradicts the assumption that deliberation is fostered by technocratic 'behind closed door' decision‐making. In the GMO case, the top‐down imposition of epistemic authority has only increased politicisation contributing to the de‐legitimation of all EU institutions involved in GMO regulation. The recent EU reform on national opt‐outs is not sufficient to address this problem. A successful reform should mitigate the negative effects of both politicisation and scientification.